Oocyte retrieval at 140-mmHg negative aspiration pressure: A promising alternative to flushing and aspiration in assisted reproduction in women with low ovarian reserve - Aswathy Kumaran; Pratap Kumar Narayan; Praveena Joglekar Pai; Amar Ramachandran; Basil Mathews; Satish Kumar Adiga (Wolters Kluwer Medknow Publications, 2015)
Background: Oocyte retrieval in women with low ovarian reserve is challenging and often results in poor pregnancy outcomes. Aim: The aim was to compare outcomes of oocyte retrieval using three aspiration methods in women with normal and low antral follicle counts (AFCs). Study Design: Retrospective cohort study. Setting: Tertiary care hospital. Materials and Methods: Data from 172 women who underwent in-vitro fertilization/intracytoplasmic sperm injection over 3 years was studied after dividing into three groups: Group A (96) - normal AFC (≥10), direct oocyte retrieval at 120 mmHg, Group B (41) - low AFC (<10), direct retrieval at 140-mmHg, Group C (35) - low AFC, follicular flushing, and aspiration at 120-mmHg. In each group, oocyte yield, embryo quality, and pregnancy out comes were assessed. Results: The oocyte and embryo yield in Groups A and B were comparable (P > 0.05) but were significantly less in Group C (P < 0.05). The pregnancy rates in Groups A and B were similar (35.4%, 39%) but were significantly less (17.1%) in Group C (P < 0.05). The live birth rate was 76% in Group A, 69% in Group B, and 50% in Group C. The miscarriage rates in the three groups were 21%, 31%, and 50%, respectively. Conclusion: Direct oocyte retrieval with 140-mmHg showed significantly better oocyte yield and pregnancy outcomes compared to flushing and aspiration in women with low AFC.